IMPORTANCE OF TYPES OF MACHINE LEARNING (Modern education and development, 2025)
This article analyzes the main types of machine learning and their importance in society. Machine learning technology, as an important part of artificial intelligence, is being effectively used in various fields. Types of machine learning, such as supervised learning, unsupervised learning, iterative learning, and reinforcement learning, play an important role in creating innovations in self-driving systems, healthcare, finance, education, and other areas.